2015
DOI: 10.1016/j.ssci.2014.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Common hazards and their mitigating measures in work zones: A qualitative study of worker perceptions

Abstract: Road construction and maintenance activities present challenges for ensuring the safety of workers and the traveling public alike. Hazards in work zones are typically studied using historical crash records but the current study took a qualitative approach by interviewing 66 workers from various work zones in Queensland, Australia. This supplemented and enhanced the limited available data regarding the frequency and nature of work zone crashes in Australia, provided worker insights into contributing factors, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Existing studies in literature recognize that workers performing their job during night shifts may see affected their performance depending on the job being performed [ [34] , [35] , [36] ]. Specifically, in the context of construction projects, the use of night shifts has been related to negative outcomes when compared with day shifts, such as the higher risk of injuries and accidents [ 37 ], lack of sleep from construction workers [ 38 ], and loss of productivity [ 39 ].…”
Section: Research Backgroundmentioning
confidence: 99%
“…Existing studies in literature recognize that workers performing their job during night shifts may see affected their performance depending on the job being performed [ [34] , [35] , [36] ]. Specifically, in the context of construction projects, the use of night shifts has been related to negative outcomes when compared with day shifts, such as the higher risk of injuries and accidents [ 37 ], lack of sleep from construction workers [ 38 ], and loss of productivity [ 39 ].…”
Section: Research Backgroundmentioning
confidence: 99%
“…Many researchers have put efforts in studying this topic (Ardeshiri and Jeihani, 2014;Brewer et al, 2006). Some researchers conducted a survey questionnaire to investigate drivers' compliance rate in different driving scenarios (Debnath et al, 2015;Weng and Meng, 2012;Mohammadi et al, 2011). However, some literatures found that drivers' compliance rate abstracted from the results of the questionnaire survey results was higher than real drivers' compliance rate in most cases, which shows that survey-based compliance rates are not very convincing enough (Lajunen and Summala, 2003;Wåhlberg et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have focused on work zone safety (e.g., [10,11]). A variety of interventions and standards, including those aimed at worker education [12], raising public awareness [13], increasing the presence of law enforcement [14], enhancing infrastructure and signage [15], and connecting vehicles to smart communication [16,17], have been suggested to improve the safety and stability in work zones. In 2009, the Federal Highway Administration published the Manual on Uniform Traffic Control Devices (MUTCD) [18].…”
Section: Literature Reviewmentioning
confidence: 99%